The Chomsky effect : a radical works beyond the ivory tower - Barsky, Robert F. (orient Blackswan, 2007)
"Noam Chomsky, writes Barsky, is an inspiration and a catalyst. Not just an analyst or advocate, he encourages people to become engaged - to be "dangerous" and challenge power and privilege. The actions and reactions of Chomsky supporters and detractors and the attending contentiousness can be thought of as "the Chomsky effect." Barsky discusses Chomsky's work in such areas as language studies, media, education, law and politics, and identifies Chomsky's intellectual and political precursors. He charts anti-Chomsky sentiments as expressed from various standpoints, including contemporary Zionism, mainstream politics, and scholarly communities. Finally, Barsky considers the role of the public intellectual in order to assess why Noam Chomsky has come to mean so much to so many - and what he may mean to generations to come."--BOOK JACKET.